Fragments of truth : residential schools and the challenge of reconciliation in Canada - Angel, Naomi, 1977-2014 (Duke University Press, 2022)
"Fragments of Truth is Naomi Angel's analysis of the Canadian Truth and Reconciliation Commission, which was established in 2008 to document the abuses of the Indian residential school system and to provide opportunities of reconciliation between Indigenous and non-Indigenous communities. Focusing on visual media, this book examines how the Commission, itself a fraught project, served as a vehicle through which memory, trauma, and visuality were able to surface in often startling ways. Angel explores how archival images of the residential schools produced by the Canadian government have been reclaimed by Indigenous communities, thereby pointing to the unstable and shifting nature of what documentation of abuse signifies. The Commission thus offers a unique optic through which to survey the long history of colonial oppression of First Nations populations"--